2011
DOI: 10.1021/jm101619e
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Syntheses and Antiproliferative Activities of Racemic, Natural (−), and Unnnatural (+) Glyceollin I

Abstract: A 14-step biomimetic synthetic route to glyceollin I (1.5% overall yield) was developed and deployed to produce the natural enantiomeric form in soy, its unnatural stereoisomer, and a racemic mixture. Enantiomeric excess was assessed by asymmetric NMR shift reagents and chiral HPLC. Antiproliferative effects were measured in human breast, ovarian, and prostate cancer cell lines, with all three chiral forms exhibiting growth inhibition (GI) in the low to mid μM range for all cells. The natural enantiomer, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 117 publications
4
34
0
1
Order By: Relevance
“…A consequent challenge is to develop feasible synthetic technologies to make the libraries. A number of technologies have been developed for chemical syntheses (20), biological syntheses (21)(22)(23), and biomimetic syntheses (24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…A consequent challenge is to develop feasible synthetic technologies to make the libraries. A number of technologies have been developed for chemical syntheses (20), biological syntheses (21)(22)(23), and biomimetic syntheses (24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…One of the CD3's most interdisciplinary projects has involved three-way collaboration with the US Department of Agriculture (USDA) and Tulane University to pursue unique natural products derived from stressed soybeans. These compounds have potential anticancer effects as well as other therapeutic possibilities [4]. Promising advanced stage projects today include three UT technologies and one from a small company contractor that are nearing the point where we will be selecting a compound for each to be moved into preclinical development.…”
Section: Accomplishments and A Glimpse At Today's Projectsmentioning
confidence: 99%
“…Instead of the expected placement on a straight line, atom positions are phase-modulated and generate a structural array reminiscent of a castle or city wall's defensive battlement, with alternating high and low regions of electron density. Incidentally, the stamp's date of issue is also the birthday of Herbert Hauptman , the American mathematician who shared with Switzerland opted to philatelically honor the IYCr on 6 March 2014 by issuing a pair of stamps [4,5] showing eye-catching mineral samples. Modern crystallography may have started with von Laue and the Braggs, but the shape and color of crystals found in nature, from snowflakes to gemstones, have captivated people from all walks of life for centuries.…”
Section: Successful Drug Discoverymentioning
confidence: 99%
“…isomer, but not the unnatural (+) Gly isomer, significantly inhibited the growth of ER -breast and ovarian tumors as well as androgen receptor-negative (AR -) prostate tumors in vitro, but to a lesser extent than its inhibition of ER + and AR + tumors (Khupse et al 2011). Further evidence for a potential ER-independent mechanism came from experiments that showed the ability of Glys to suppress tumorigenesis in triple-negative breast carcinoma cells (MDA-MB-231 and MDA-MB-468) that lack ERs, PgR and human epidermal growth factor receptor 2 (Her2) .…”
Section: Glys Antitumor Effectsmentioning
confidence: 97%
“…The natural (-) Gly I isomer also showed the highest growth inhibition activity against ER + breast and ovarian tumors as well as androgen receptor-positive (AR + ) prostate tumors in vitro, compared to a Gly racemic mixture and unnatural (+) Gly I isomer (Khupse et al 2011). In contrast to the aforementioned anti-estrogenic effects of Glys, one study reported estrogenic effects of Glys, increasing the proliferation of ER + MCF-7 cells, mainly through activity at ERβ (Kim et al 2010a).…”
Section: Glys Antitumor Effectsmentioning
confidence: 99%